Apply the Sturm-Liouville Problem With Green’s Function to Linear System - Hassan, Abdelgabar Adam; Ahmed, Shams A. (Communications in Mathematics and Applications, 2021)
In this paper, we will study the Sturm-Liouville problem, we find the eigenvalues are the solution of the Sturm-Liouville problem and the eigenfunctions are corresponding solutions. Thus, we study construction of the Green’s function to solving the first order differential \(n\)-dimensional linear system, and application for Fourier series, and we show that the Green’s function solution to the two and three-dimensional Laplace and Poisson equations.